Learning Path : Go Fundamentals - Roumeliotis, Rachel (O'Reilly Media, Incorporated, 2015)
Go from Hello World to writing highly concurrent programs Go, the new open source language from Google, is known for its simple syntax, rich library, easy concurrency, and scalability. It's used in software systems where "scale big and run fast" is the daily mantra. As you work through real-world examples and task-based lessons, you'll learn the complete language and discover how useful Go can be